THE USE OF TASK BASED LEARNING METHOD TO ENHANCE STUDENTS’ READING COMPREHENSION AT SMP N 5 KOTA TERNATE - Nasrun, Fahria; Bahara, Susana R.; Yetty, Yetty (Universitas Khairun, 2023)
The purpose of this research was to investigate the use of task-based learning method in enhance students' reading comprehension. This research used a quantitative method. The sample consisted of 24 students of class VIII-2 SMP Negeri 5 Kota Ternate. The data collected through pretest and posttest. In collecting the data, multiple choice tests were used in the form of an instrument. The result of this research shown that the result of posttest scores higher than pretest. The average score of students’ pretests was 51.875 while the average score of posttests was 75.25. The t-statistical value was 7.81 which was higher than t-critical value 1.714 at significance level (0,05) and the degree of freedom of 23 used one tailed test. Based on the data, it was found that using task-based learning can enhance students’ reading comprehension. The students have a positive response to task-based learning as a method to improve students' ability in reading comprehension. It can be seen that there is a significant difference between the pre-test and post-test results.